Examen crítico de los diferentes tipos de estado y el derecho a castigar - Falcón y Tella, Fernando (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
The main object of this investigation is the basis and goal of punishment considering the right to punish from a critical point of view. Studies and works regarding punishment are scarce when we compare them to those related to Crime Theory or some aspect thereof. To this end, we review the main doctrines regarding this subject, around which have been developed different sorts of schools: absolutist-retributive, and relativist preventive, both general and special, in all their different forms, under the aegis of the State, also differently conceived.
Keywords: Punishment; Crime; Retribution; Prevention; Rechtstaat; Welfare State